Achievements of NEDO Durability Projects on SOFC Stacks in the Light of Physicochemical Mechanisms1. Issue 4 (3rd June 2019) - Yokokawa, H.; Suzuki, M.; Yoda, M.; Suto, T.; Tomida, K.; Hiwatashi, K.; Shimazu, M.; Kawakami, A.; Sumi, H.; Ohmori, M.; Ryu, T.; Mori, N.; et al.
Abstract: Achievements of NEDO durability projects on SOFC mode are summarized with a focus on the physicochemical mechanisms characterized by diffusion properties of cell components and chemical reactions of cell components with gaseous impurities. Ni sintering and depletion including impurity (P, B, S) effects have been examined in terms of the surface/interface energies of Ni/oxide cermet anodes. The conductivity degradation due to the transformation of the cubic YSZ electrolyte was found to be characterized in terms of two time constants for the reductive and the oxidative regions to be determined by the Y‐diffusivity and its enhancement on NiO internal reduction in YSZ, while observed gaps in conductivity degradation behavior between stacks and button cells were ascribed to differences in those physicochemical properties involved, namely cation diffusion and kinetics associated with NiO internal reduction. The cathode performance degradation due to sulfur poisoning exhibits a variety of dependences on the microstructure (dense or porous) of doped‐ceria interlayers, the thickness of YSZ electrolyte and the humidity in the anode atmosphere, suggesting effects of protons in the cathode vicinity and the SrO activity changes during fabrication the LSCF/GDC/YSZ multilayers. Some defect chemical considerations were made on how such defects are affected by fabrication processes.